Immune Checkpoint Molecules Expressed on CD4+ T Cell Subsets in Chronic Asymptomatic Hepatitis B Virus Carriers With Hepatitis B e Antigen-Negative - Cui, Dawei; Jiang, Daixi; Yan, Cuilin; Liu, Xia; Lv, Yan; Xie, Jue; Chen, Yu (Frontiers in Microbiology, 2022)
Background: Chronic hepatitis B virus (HBV) infection remains a major public health problem worldwide. Immune checkpoint molecules expressed on CD4+T cells play critical roles in chronic HBV infection. However, their roles in chronic asymptomatic HBV carriers (ASCs) with hepatitis B e antigen (HBeAg)-negative remain unclear. Here, we explore the role of immune checkpoint molecules expressed on CD4+T cell subsets in chronic ASCs with HBeAg-negative. Method: Human peripheral blood mononuclear cells (PBMCs) from the chronic asymptomatic HBV carriers with HBeAg-negative and healthy controls (HC) were isolated, and immune checkpoint molecules expressed on CD4+T cell subsets, and serum cytokines were detected by flow cytometry. Moreover, the mRNA expressions of immune checkpoint molecules were analyzed by real-time quantitative PCR assay. Result: In comparison with HC, CD4+T cells highly expressed LAG-3, TIM-3, and PD-1 in PBMCs from chronic ASCs with HBeAg-negative. Interestingly, the expressions of TIM-3 and PD-1 on circulating follicular helper T (Tfh) cells in ASCs were significantly high, respectively. Moreover, high expressions of LAG-3, TIM-3, and PD-1 were obviously different among Treg, Th1, Th2, and Th17 cells, respectively. Additionally, the expressions of TIM-3 and CTLA-4 mRNA in PBMCs from ASCs were significantly elevated. However, the frequency of CTLA-4+CD4+T cell subsets in PBMCs from ASCs was not different from HC. The levels of six cytokines in serum from ASCs were not obviously different from HC. Conclusion: Immune checkpoint molecules highly expressed on CD4+T cell subsets indicated an important role in chronic ASCs with HBeAg-negative, which provided potential therapeutic targets in the pathogenesis of chronic HBV infection.